Mission-Oriented Sensor Networks and Systems: Art and Science Volume 1: Foundations - Ammari, Habib M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses topics in mission-oriented sensor networks and systems research and practice, enabling readers to understand the major technical and application challenges of these networks, with respect to their architectures, protocols, algorithms, and application design. It also presents novel theoretical and practical ideas, which have led to the development of solid foundations for the design, analysis, and implementation of energy-efficient, reliable, and secure mission-oriented sensor network applications. Covering various topics, including sensor node architecture, sensor deployment, mobile coverage, mission assignment, detection, localization, tracking, data dissemination, data fusion, topology control, geometric routing, location privacy, secure communication, and cryptograph, it is a valuable resource for computer scientists, researchers, and practitioners in academia and industry.
Introduction -- Sensor Node Architectures and Design Considerations -- Failure Handling in RPL Implementations: An Experimental Qualitative Study -- On the Optimization of WSN Deployment for Sensing Physical Phenomena: Applications to Urban Air Pollution Monitoring -- Mobile Coverage -- Energy Aware Task Allocation in WSNs -- Sensor Assignment to Missions -- Resource Allocation and Task Scheduling in Cloud of Sensors -- Location Privacy in Sensor Networks -- Data-driven Detection of Sensor-hijacking Attacks on Electrocardiogram Sensors -- Cryptography.
Keywords: Telecommunication; Control engineering; Robotics; Automation; Communications Engineering, Networks; Control, Robotics, Automation; Control and Systems Theory